Machine-Learning-Driven Physiological Identity Verification Frameworks within Risk-Coverage Sector: High-Integrity Access Validation, Policy Adherence (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The rapid digitization of the risk-coverage sector, including insurance and financial protection systems, has intensified the need for robust identity verification mechanisms that ensure secure access, fraud prevention, and regulatory compliance. Traditional authentication systems, primarily reliant on static credentials, are increasingly inadequate against sophisticated threats such as identity theft, impersonation, and biometric spoofing. This paper proposes a comprehensive machine-learning-driven physiological identity verification framework that integrates multimodal biometric signals, including speech characteristics, heart rate variability (HRV), and behavioral physiological markers, to enhance authentication accuracy and system integrity.The study synthesizes theoretical principles from speech signal processing, acoustic modeling, and physiological monitoring to develop a hybrid verification architecture. Foundational techniques such as Mel-frequency cepstral coefficients (MFCC), articulatory feature modeling, and vocal tract resonance analysis are integrated with physiological indicators like electrocardiogram (ECG)-derived HRV and EEG-based cognitive state detection. Machine learning models, including supervised classification and adaptive feature modeling, are applied to extract discriminative identity patterns across modalities. The framework further incorporates adaptive policy compliance mechanisms aligned with regulatory requirements in the insurance sector.The proposed system addresses key challenges including variability in biometric signals, environmental noise, user-state dependency (e.g., fatigue), and adversarial spoofing attempts. Through analytical modeling and simulated evaluation, the framework demonstrates improved resilience, higher authentication precision, and enhanced robustness against fraud scenarios compared to unimodal systems. The integration of physiological and behavioral signals enables continuous authentication, thereby reducing reliance on one-time verification.The findings suggest that multimodal machine-learning-based physiological verification systems can significantly strengthen identity validation processes in high-risk environments. However, challenges related to data privacy, computational overhead, and system scalability remain critical considerations. This research contributes a novel interdisciplinary framework bridging speech processing, biomedical signal analysis, and machine learning, offering a scalable pathway for secure and compliant identity verification in modern risk-coverage infrastructures.